Music learning and the use of DICT in a community of practice: A research in a community choir - Soares, Eldom; Marins, Paulo Roberto Affonso (Revista Hipótese, 2022)
The general objective of this research was to analyze the use of Digital Information and Communication Technologies (DICT) in musical learning in a community choir, being this choir understood as a "Community of Practice". As specific objectives, this research sought to understand the characteristics of a Community of Practice and to analyze the contribution of DICT in the process of choral preparation for a concert. The method adopted was Action-Research, in which several actions were proposed and executed to solve issues related to the rehearsal process of the choir. Three theoretical perspectives were used to analyze the data: Situated Learning, Communities of Practice (COP), and the "Flipped Classroom" methodology. In the end, the name "Expanded Rehearsal" is proposed for the rehearsal methodology developed based on applying the principles of the "Flipped Classroom" in choral practice.
Keywords: DICT; Community of practice; Flipped classroom